Surface engineering for corrosion and wear resistance - Davis, J. R. (Joseph R.) (ASM International : Institute of Materials, 2001)
Engineers are faced with a bewildering array of choices when selecting a surface treatment for a specific corrosion or wear application. This book provides practical information to help them select the best possible treatment. An entire chapter is devoted to process comparisons, and dozens of useful tables and figures compare surface treatment thickness and hardness ranges; abrasion and corrosion resistance; processing time, temperature, and pressure; costs; distortion tendencies; and other critical process factors and coating characteristics. The chapter Practical Guidelines for Surface Engin.